Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1063/1.3244206
|View full text |Cite
|
Sign up to set email alerts
|

Large energy soliton erbium-doped fiber laser with a graphene-polymer composite mode locker

Abstract: Due to its unique electronic property and the Pauli Blocking Principle, atomic layer graphene possesses wavelength-independent ultrafast saturable absorption, which can be exploited for the ultrafast photonics application. Through chemical functionalization, a graphene-polymer nanocomposite membrane was fabricated and firstly used to mode lock a fiber laser. Stable mode locked solitons with 3 nJ pulse energy, 700 fs pulse width at the 1590 nm wavelength have been directly generated from the laser. We show that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
252
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 472 publications
(254 citation statements)
references
References 13 publications
2
252
0
Order By: Relevance
“…We had experimentally measured the saturation intensity of graphene at 1.06 µm and 1.56 µm, respectively. It varies from 0.87 MW* cm −2 at 1.06?m to 0.71 MW*cm −2 at 1.56 µm 13,15,16 .…”
Section: Graphene Mode-locked Fiber Lasermentioning
confidence: 98%
“…We had experimentally measured the saturation intensity of graphene at 1.06 µm and 1.56 µm, respectively. It varies from 0.87 MW* cm −2 at 1.06?m to 0.71 MW*cm −2 at 1.56 µm 13,15,16 .…”
Section: Graphene Mode-locked Fiber Lasermentioning
confidence: 98%
“…[9][10][11][12] Furthermore, some of these nanomaterials are also used as optical absorber for ultrafast photonics, such as passive Q-switcher, optical limiter, and mode locker, because of their broadband nonlinear optical response if under high power laser illumination. [13][14][15][16][17] However, these nanomaterials are limited in its applications for optoelectronic devices because of their intrinsic energy bandgap. Very recently, black phosphorus (BP) as a rising 2D material has raised much attention owing to its relatively higher carrier mobility, and more…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the carrier relaxation processes in graphene have ultrafast time constants. In view of the unique broad band absorption property of graphene, Xia et al have firstly fabricated an ultra-fast graphene based photo-detector with ultrafast response [4]; In previous papers we have also experimentally demonstrated that the wideband absorption of graphene could become saturated under intensive illumination [5,6,7,8,9]. Taking advantage of the saturable absorption property of graphene, we have further demonstrated mode-locking of an erbium-doped fiber laser and a diode-pumped Nd:YAG ceramic laser, operating at the wavelength of 1.56 m and 1064 nm, respectively, with few layer graphene [9].…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the saturable absorption property of graphene, we have further demonstrated mode-locking of an erbium-doped fiber laser and a diode-pumped Nd:YAG ceramic laser, operating at the wavelength of 1.56 m and 1064 nm, respectively, with few layer graphene [9]. We fabricated graphene-polymer nano-composite membrane to achieve soliton mode locking with per-pulse energy up to 3 nJ in anomalous dispersion cavity [8] and used atomic layer graphene to obtain large energy mode locking with single pulse energy as high as 7.3 nJ [7]. However, wavelength-tunable graphene based mode locking in various dispersion regimes have not been reported.…”
Section: Introductionmentioning
confidence: 99%